Evaluasi User Experience pada Aplikasi BCA Mobile dan MyBCA dengan menggunakan Metode Usability Testing dan User Experience Questionnaire (UEQ) - Hansen Natanael; Aryo Pinandito; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
BCA Mobile and MyBCA are two mobile banking apps offered by BCA. Users of BCA Mobile have complained about issues with signal indicator lights, a large number of steps required and a lack of a "share" feature. On the other hand, MyBCA is favored by users due to its modern and attractive appearance, biometric login feature, and fast speed. However, it has limited features and a difficult registration process. This study used usability testing and Single Ease Questionnaire (SEQ) to measure the effect of the number of clicks and duration on user satisfaction for both apps. It also used the User Experience Questionnaire (UEQ) to measure user satisfaction based on attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The study found that there were differences in the number of clicks and duration between both apps, with MyBCA having a lower average number of clicks and a shorter average duration. However, there was no difference in satisfaction between the two apps. The number of clicks and duration had no effect on user satisfaction for either app. The study revealed there are differences in attractiveness, efficiency, stimulation, and novelty, but no differences in perspicuity and dependability between the two apps. MyBCA had higher average scores on all UEQ factors compared to BCA Mobile, indicating that these factors influence user satisfaction for both apps.